Effects of Xanthan Gum on the quality and staling of kutsinta (Brown Rice Cake) - Garcia, Francesca Louise P.; Cornago, Djanna F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
Kutsinta, or brown rice cake, is a steamed traditional Philippine rice cake prepared from wet-milled rice flour, sugar, and lye water. This study aimed to determine the effect of xanthan gum on the quality and staling behavior of kutsinta during storage for two days at refrigerated temperature. Through sensory evaluation, the level of xanthan gum incorporation resulting in the most acceptable kutsinta was established and found to be 0.1% (rice weight basis). Consumer acceptance and intensity ratings for various sensorial parameters were determined and physico-chemical tests (measurement of weight and water activity) were performed to examine quality changes and staling behavior of kutsinta. Texture profile analysis was also conducted to obtain objective measurements on the differences in textural properties of the samples throughout the storage period. Incorporation of xanthan gum had no significant effect on the acceptability of the sensory characteristics of kutsinta, which decreased significantly (p<0.05) on each storage day except for odor and flavor. Intensity ratings did not significantly change across days with the addition of xanthan, except for color which was significantly lighter for xanthan-treated samples on the second day. Xanthan-containing samples exhibited lower weight loss values during storage, indicating higher water retention. Water activity values were not significantly affected by gum incorporation and changed erratically across days. Xanthan had no significant effect on the textural properties of kutsinta. Adhesiveness, however, was higher for xanthan-treated samples. Hardness 1 and 2, adhesiveness, gumminess, and chewiness values increased significantly after a day of storage. Overall, xanthan gum incorporation had no significant effect on kutsinta quality throughout its storage period. Although not significant, xanthan reduced weight loss, and hence improved moisture retention of samples. Determination of the moisture content and retrogradation enthalpies of the samples is recommended to further examine the effects of xanthan gum on the staling behavior of kutsinta.
Thesis Classification: P
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Rice cakes -- Philippines; Xanthan gum